Legal Implications of the Implementation of the Financial Services Authority Licensing Requirement for Foreign Venture Capital Companies under the P2SK Law - I Made Maswinartha; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The growth of the digital economy in Indonesia has positioned Foreign Venture Capital Companies (FVCCs) as a fundamental pillar within the startup financing ecosystem. However, the legal landscape has undergone a significant transformation with the enactment of Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law). This regulation mandates that all financial services business actors, including foreign entities, obtain business licenses from the Financial Services Authority (Otoritas Jasa Keuangan/OJK). This study aims to analyze the legal implications of this licensing requirement on business certainty for foreign investors and to examine the normative inconsistencies between the Investment Law and the P2SK Law. This research employs a normative juridical method with a statutory approach and a conceptual approach. The findings reveal the existence of normative ambiguity (vagueness of norms) concerning the operational status of FVCCs utilizing offshore structures during the regulatory transition period, which is set to expire in January 2026. Such legal uncertainty has the potential to hinder the inflow of Foreign Direct Investment (FDI) if not promptly addressed through adaptive implementing regulations, such as the optimization of regulations governing Foreign Representative Offices. On the other hand, the licensing obligation enhances legal certainty by providing preventive legal protection for Business Partner Companies through contract standardization and integrated supervision. In conclusion, this study recommends cross-sectoral regulatory harmonization and the issuance of clear technical guidelines to ensure a balanced approach between prudential supervision and investment facilitation.